(untitled) (International Journal of Scientific Pediatrics, 2025)
Annotation. Children with congenital heart defects constitute a highly susceptible cohort for the development of intestinal dysbiosis and epithelial barrier dysfunction. This athophysiological vulnerability stems from anomalous intestinal perfusion or hypoxemia, which manifests in conditions of low cardiac output or cyanosis. Disruption of gut microbiota eubiosis potentially exacerbates systemic inflammation, adversely affecting clinical outcomes in this patient group. Despite significant advancements in therapeutic strategies and survival rates for patients with congenital heart defects, the incidence of associated complications remains substantial, raising questions regarding the microbiome’s role in the pathogenesis of inflammatory processes. Aim of the study: to analyze the characteristics, properties, mechanistic role, and diagnostic methods of short-chain fatty acids in assessing the state of the intestinal microbiocenosis in children with congenital heart defects, based on data from international and domestic research. Material and methods: a systematic literature review on the specified topic was conducted using electronic database resources including PubMed, Medline, eLibrary, Scopus, Web of Science, and Cochrane Library. Results and discussion: the obtained data provide a comprehensive understanding of the properties and composition of the intestinal microbiota in children with congenital heart defects. They emphasize the necessity of studying the microbiota not as an isolated organ, but as an integral system that supports interaction with all physiological systems of the body and plays a key role in maintaining homeostasis and adaptive reserves to changing internal and external environmental conditions. It has been determined that congenital heart defects remain the primary cause of child mortality, despite treatment advancements. In children with congenital heart defects, inflammation and low cardiac output are crucial pathophysiological factors exacerbating clinical outcomes. These conditions contribute to gut microbiome dysbiosis, leading to a decrease in the production of short-chain fatty acids such as acetate, propionate, and butyrate. As primary metabolites of beneficial microflora, they are critically important for maintaining intestinal homeostasis, including cell metabolism, barrier function, and systemic influence. The dysbiosis identified in children with these defects is caused by hypoxia, stress, antibiotics, and nutritional factors, which leads to a decrease in butyrate and propionate. Gas chromatography-mass spectrometry is an effective method for diagnosing short-chain fatty acids. A comprehensive assessment of the short-chain fatty acids profile in children with heart defects opens new avenues for improving diagnosis, prognosis, and optimizing therapeutic approaches aimed at correcting the microbiome and improving outcomes. Conclusions: potential interactions between congenital heart defects and the microbiome are illustrated, key signaling mechanisms are discussed, along with promising research directions and opportunities for the therapeutic translation of fundamental scientific data.